Strategi Pencegahan Radikalisme Di Pondok Pesantren Jam’iyyah Islamiyyah - Siti Rachmah Amalia; Nazriah Nurunajwa (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
This study describes the efforts of Islamic religious education teachers in preventing radicalism in the Jam'iyyah Islamiyyah Islamic boarding school, Tangerang City. This is about the strategies or efforts of Islamic religious education teachers in preventing radicalism in the Jam'iyyah Islamiyyah Islamic boarding school, Tangerang City. In addition, what are the supporting factors for the efforts of the Jam'iyyah Islamic boarding school in preventing radicalism from the environment, learning and so on. This study used a qualitative approach with a descriptive method in which data were obtained from the field and books related to this discussion.